On-ground testing of the role of adhesion in the LISA-Pathfinder test mass injection phase. Issue 10 (15th May 2017) - Bortoluzzi, D.; Zanoni, C.; Conklin, J.W.
Highlights: Metallic adhesion can affect the injection of a body into a geodesic trajectory. A measurement facility is built to characterize the behaviour of gold cold weldings. The facility representativeness and the results analysis technique are improved. Good accuracy performances allow to measure binding force to elongation functions. Estimated adhesion contribution to the proof mass velocity is refined. Abstract: Many space missions share the need to fly a free-falling body inside the spacecraft, as a reference for navigation and/or as a probe for the local gravitational field. When a mechanism is required to cage such an object during the launch phase, the need arises to release it to free-fall once the operational phase must be initiated in orbit. The criticality of this phase increases when the mechanical interfaces between the body and the mechanism are affected by adhesion and the actuation authority of the control system on the free-falling body is limited. Both conditions are realized in the LISA Pathfinder mission, which aims at injecting a gold-coated 2 kg cubic test mass into a nearly perfect geodesic trajectory to demonstrate the readiness of the developed technology for in-space gravity wave detection. The criticality of adhesion is widely recognized in space technology, because it can affect and jeopardize the functionality of mechanisms, when arising between moving parts. In the LISA Pathfinder case, metallic adhesion potentially plays a relevant role, mainly for two reasons. First, thanks to its properties (ductility, high surface energy) the gold coating on the proof mass easily produces cold weldings, especially in vacuum conditions. Second, the detachment of the proof mass from the releasing device occurs abruptly and a relevant influence of the separation velocity is expected on the strength of the welding. This can produce an excessive velocity of the proof mass at the retraction of the releasing device for the following capture and centring phase on behalf of the control system. A testing activity is performed to characterize the dynamic behaviour of the adhesive bonds between the proof mass and the releasing device, which can be used to predict their contribution on the residual velocity of the proof mass after in-flight release. The study of such a dynamic phenomenon sets some challenging requirements on the measurement technique, both on the instrumental and on the signal analysis sides. However, the recent improvements on the testing activities make it possible to refine the contribution of adhesion on the proof mass velocity budget at the release. In this paper we describe the recent experimental results, the developments in the measurement technique, the improvements in the repeatability of the results and the related projection to in-flight release dynamics, in comparison with the previous results.